Combined individual and family therapy in comparison to treatment as usual for people at‐risk of psychosis: A feasibility study (IF CBT): Trial rationale, methodology and baseline characteristics. Issue 1 (26th December 2019) - Law, Heather; Izon, Emma; Au‐Yeung, Karmen; Morrison, Anthony P.; Byrne, Rory; Notley, Caitlin; Yung, Alison; Norrie, John; French, Paul
Abstract: Aims: Current National Institute for Health and Care Excellence (NICE) guidelines for psychosis recommend psychological therapy with or without family intervention for individuals at‐risk of developing psychosis. NICE guidelines have a specific research recommendation to investigate the clinical and cost effectiveness of combined individual and family intervention. We report the rationale, design and baseline characteristics of a feasibility study which aimed to investigate combined Individual and Family Cognitive Behavioural Therapy (IFCBT) for those at‐risk of developing psychosis. Methods: The IFCBT study was a single blind, pilot randomized controlled trial (RCT) to compare a combined individual and family Cognitive Behavioural Therapy (CBT) intervention to treatment as usual. Participants were assessed using the Comprehensive Assessment of the At‐risk Mental State (CAARMS) and randomly allocated to either therapy or enhanced treatment as usual (ETAU). All participants were followed up at 6 and 12 months. Primary feasibility outcomes were recruitment and retention of participants. Secondary outcomes included transition to psychosis and assessment of mood, anxiety and the relationship of the individual and nominated family member. Results: We report data showing entry into the study from initial enquiry to randomization. We report the characteristics of the recruited sample of individuals (n = 70) and family members (n = 70) at baseline. Conclusions: The study recruited to 92% of target demonstrating it is feasible to identify and recruit participants. Our study aimed to add to the current evidence base regarding the utility of family interventions for people at‐risk of psychosis.